Destination unknown - Christie, Agatha (HarperCollins, 2017)
A young woman with nothing to live for is persuaded to embark on a suicide mission to find a missing scientist. When a number of leading scientists disappear without trace, concern grows within the international intelligence community. Are they being kidnapped? Blackmailed? Brainwashed? One woman appears to have the key to the mystery. Unfortunately, Olive Betteron now lies in a hospital bed, dying from injuries sustained in a Moroccan plane crash. Meanwhile, in a Casablanca hotel room, Hilary Craven prepares to take her own life. But her suicide attempt is about to be interrupted by a man who will offer her an altogether more thrilling way to die.